PENGARUH PROFITABILITAS, SET KESEMPATAN INVESTASI, PERTUMBUHAN PENJUALAN DAN RISIKO BISNIS PADA STRUKTUR MODAL - Lia Erosvitha, Cicilia Kadek; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2016)
The value of the company will be achieved, if the company is able to manage an efficient capital structure. Maximizing the value of the company can be done by increasing the company's capital structure. The purpose of this study was to determine the effect of profitability, investment opportunity set, sales growth, and business risk in the capital structure. This research was conducted on all food and beverages company in Indonesia Stock Exchange. The samples used were 12 companies from the population of 16 companies, through purposive sampling method. The analysis technique applied is a technique of multiple linear regression analysis. The results showed that the profitability of a significant negative effect on the capital structure, the investment opportunity set and sales growth significant positive effect on the capital structure, while the business risk has no effect on the capital structure
Keywords: Profitability, Investment Opportunity Set, Sales Growth, Business Risk, Capital Structure.